The Use of Phonetically Reduced Modals in Present-day English: A Corpus-Based Analysis - Ikmi Nur Oktavianti (Universitas Ahmad Dahlan, 2018)
This paper examines the usage frequency of phonetically reduced modals (i.e. gonna, wanna, gotta) in Present-day English. It is assumed that in distinct sociolinguistic and discourse contexts, the use of reduced modals is dynamic. To collect the data, there are two corpora used in this study, Corpus of Contemporary American English and Global Web-Based English as the representatives of Present-day English. The analysis focuses on usage frequency of phonetically reduced modals over period of time, in different regions, different medium of language use, and different text types. The frequencies were further interpreted based on sociolinguistics and text genre perspective to reveal the factors triggering the dynamic of use. The results of this study show the use of reduced modals is dramatically escalating in the last decades. According to regional observation, the use of reduced modals is more frequent in the United States than in other English-speaking countries. In relation to medium of language use, reduced modals are more commonly used in spoken language than in written language. As for text type, the usage frequency of reduced modal in fiction texts is the highest compared to academic texts and news texts. Academic texts seem to avoid these linguistic units since this sort of text must obey the use of standard language in which reduced forms are less standard and more colloquial. This phonetic reduction is plausible to occur since language system and language use apply economy principle. The use of phonetically reduced modals, however, varies in different context, varies in different context, influenced by colloquialization: the more colloquial the context is, the more frequent they are. In general, language use is phonetically simplified and sociolinguistically colloquialized.